Interactive Animation Learning Media on Android as a Creative Learning in Regression Analysis Topic - Ayuni, Ni Wayan Dewinta (JTP - Jurnal Teknologi Pendidikan, 2022)
Technology has a significant role to build the quality of education which is one of the world’s purpose in sustainable development goals in 2015-2030 by United Nations. The implementation of technology in education is to develop the learning media. The purpose of this study is to create interactive animation learning media that can be accessed using Android Smartphone as one of creative learning alternative in online learning. This media was applied in Statistics Subject, Regression Analysis Topic, Accounting Department of Politeknik Negeri Bali. The method used in this research was research and development (R&D). There were some steps in this research which are (1) planning and designing; (2) production and editing; (3) validating and revision; (4) implementation; and (5) evaluation step. The first step was planning and designing. In this step, the animation characters, background, color theme, and storyboard were determined. The next step was production and editing step. After that the validation steps were done. There were three validators in this research, which were Statistics Expert, Statistics Lecturer, and Media expert. The validation score of this media was 95.33 that was classified as a very good learning media and proper to be implemented. The next step was revising step as the validators’ suggestion. The learning media then was implemented in experiment class using hybrid learning environment. And as the last step, the evaluation step was done by comparing the analysis test score of experiment class and the control class. The method used in evaluation step was two independent sample t-test. As conclusion, this media can improve the ability of student in Statistical Analysis.